Rationally design of 2D branched Ni(OH)2/MnO2 hybrid hierarchical architecture on Ni foam for high performance supercapacitors. (1st June 2019) - Tian, Liangliang; Xia, Kaidong; Wu, Shenping; Cai, Yanhua; Liu, Hongdong; Jing, Xiaolong; Yang, Tong; Chen, Daidong; Bai, Xue; Zhou, Min; Li, Lu
Abstract: As electrode materials for supercapacitors, nanostructured hybrids always show better performance compared to corresponding single material. In this work, Ni(OH)2 flakes/MnO2 nanosheets hybrid hierarchical architecture (Ni(OH)2 /MnO2 HHA) was constructed on Ni foam (NF) through a two-step hydrothermal reaction. Interestingly, MnO2 nanosheets are vertically grown on the both sides of Ni(OH)2 flakes, forming a highly porous structure with large specific surface area and amounts of diffusion channels. As a binder-free electrode for supercapacitors, Ni(OH)2 /MnO2 HHA/NF exhibits a high specific capacity of 253.6 mAh g −1 at 2 A g −1, which is much higher than the individual Ni(OH)2 and MnO2 . The excellent electrochemical performance can be attributed to the highly porous architecture, two-dimensional (2D) feature and synergistic effect between Ni(OH)2 and MnO2 . The asymmetric hybrid supercapacitor was assembled using Ni(OH)2 /MnO2 HHA/NF (24 h) as positive electrode and activated carbon (AC) as negative electrode in 3 M KOH. The hybrid supercapacitor cell can be cycled in the voltage window of 0–1.9 V and exhibits a maximum specific energy of 29.9 Wh kg −1 at 1900 W kg −1 . The results indicate that the Ni(OH)2 /MnO2 HHA/NF electrode shows great potential in design of high-performance energy storage devices. The construction of this 2D branched hierarchical architecture provides an effective method to obtain excellent electrode materials for energy storage. Graphical abstract: Image 1